Sistem Perhitungan Insentif Pegawai Berbasis Web Kantor Kementerian Agama Kota Surabaya - Imam syafii rachmanda; Moh Noor Al Azam (Institut Teknologi Adhi Tama Surabaya, 2025)
Employee performance is one of the most important factors in the success of an organization, where motivation and productivity can be enhanced through incentives. However, in this digital era, many institutions, particularly in the government sector, remain heavily reliant on manual administrative systems that are not as efficient as expected. In several studies regarding incentives, the manual calculation process often results in various issues, including process defects, the risk of human error, and a lack of transparency, which can negatively impact the trust and confidence of employees. This issue particularly occurs at the Office of the Ministry of Religious Affairs of Surabaya City, as the incentive process, which remains manual, renders it inefficient. To address this problem, this research focuses on the development of a web-based employee incentive system. The development of this system employs the Waterfall method and implements technologies such as the Laravel framework, PHP, and MySQL to ensure that the system operates smoothly. The outcome of this research is a functional web application that successfully automates the incentive process and presents it on the web in an efficient manner. The black box method was selected as the method for testing the functionality of the system, starting with the user login process, importing data from Excel files, performing automatic calculations, modifying employee data, and generating monthly reports, which were successfully validated. This new incentive calculation system is capable of enhancing accuracy, efficiency, and transparency in the management of incentives at the Ministry of Religious Affairs Office in Surabaya.